The urban planning crime typified in article 138 of the General Law of Urbanism and Construction (Justicia &Derecho, 2024)
The text presents an analysis of a special part of the criminal type established in article 138 of the General Law of Urbanism and Constructions, postulating an interpretation of its content of objective injustice that implies the censure of the realization of illegal acts on non-urbanizable properties derived from a subdivision of land, related in this way to the undermining of urban planning, with special emphasis on the development of the aspects of imputation and sanction that derive from its assumption and that are considered more relevant for its practical application.
Keywords: Crimes; urban crime; urban law; territorial planning; special part